A BRIEF REVIEW ON CURRENT SCENARIO OF ANTIHYPERTENSIVE AYURVEDIC DRUGS - G. Uike, Shekhar; Ganvir, Rakesh M.; V. Vithalani, Lalitkumar (International Journal of Ayurveda and Pharma Research, 2018)
Now a days hypertension is most prevailing lifestyle disorder. It is also known as silent killer. Hypertension has been globally acknowledged as most prevalent risk factor for life threatening cardiovascular diseases. Ayurveda is a science of life and oldest medical science known to the mankind practised in India. Since ages Indian population have been benefited by the healing touch of this science. Due to life style of hurry, worry and curry, many lifestyle disorders become household diseases in developing countries and hypertension is one among them.Hypertension is one of such disorders which can be caused by many factors, including increase in the volume of body fluid, resistance of the blood vessels, and other factors that elevate blood pressure. Modern treatment modalities although reduce the blood pressure very effectively but their long term efficacy i.e. target organ damage reduction is not enough. Despite various new drugs the overall percentage of population suffering from hypertension is increasing day by day. The use of herbal medicine is finding more relevance with the recognition that we are facing more challenges in the treatment of some medical conditions such as hypertension.This review is regarding current on medicinal approach to deal with hypertension as well as antihypertensive actions of some herbal medicines and formulations, their therapeutic values in clinical situation and recent approaches to validate and document their antihypertensive efficacies. The central idea behind this review is that if we can demonstrate the value of our science and art of healing even in current lifestyle disorders like hypertension with proper evidence based documentation then it will not only increase faith for Ayurveda among young researchers but also enhance global acceptability of our science as a contemporary science of medicine.